COMPARISON OF MACERATION AND ULTRASONICATION METHODS ON INDIGOFERA TINCTORIA LINN LEAF EXTRACTION (Jurnal Bahan Alam Terbarukan, 2018)
The extraction of Indigofera Tinctoria Linn leaf into natural dyes was studied using two methods: maceration and ultrasonication. Other variables tested were the differences in the degree of solvent acidity used: neutral, alcoholic, acid and base. The yield and the dye strength measured by the absorbance are response to the change of those variables. The better yields were obtained from ultrasonication method compared to the maceration one. The highest yield was shown in the result of maceration method at neutral condition, 2.3%, while in ultrasonic method was at alcoholic condition 13%. The acidity of the solvent affects the resulted colour. By using maceration method and the neutral condition produced dark blue, the acid solvent produced a grey dye, the alkaline produced a greenish dye and the alcoholic produced a brownish dye. With the aid of ultrasonication, blue dye was generated on the use of neutral, acid and alcoholic solvents, whereas brownish was on alkaline solution.